Computed tomographic appearance of abdominal lymph nodes in healthy cats. (23rd March 2018) - Perlini, Michael; Bugbee, Andrew; Secrest, Scott
Abstract : Background: Computed tomography (CT) is commonly used in veterinary medicine and plays an important role in disease identification and cancer staging. Identification of abnormal abdominal lymph nodes is important for clinical, therapeutic, and prognostic decision making. No published study describes the CT appearance of abdominal lymph nodes in healthy cats. Hypothesis/Objectives: All abdominal lymph centers will be identified on CT with the majority of lymph nodes being elongated and homogenously contrast enhancing. Animals: Sixteen healthy cats without clinical or biochemical evidence of disease. Methods: Precontrast and postcontrast CT images of sedated healthy cats were used to identify the presence and descriptive characteristics of intra‐abdominal lymph nodes. These assessments then were compared with patient characteristics to identify possible correlations. Results: Abdominal lymph nodes were readily identified on CT with caudal mesenteric, colic, hepatic, inguinal, and pancreaticoduodenal lymph nodes identified in 16/16 cats. Lymph node size and shape varied among lymph centers with nearly all lymph nodes homogeneously contrast enhancing in 515/525. Significant negative correlations were identified between age and length ( P  = .0166) and width ( P  = .0387) of abdominal lymph nodes as well as age and number of sacral lymph nodes ( P  = .0493). Intranodal fat was present in 18/525 lymph nodes. Conclusions and Clinical Importance: CT readily permitted identification and characterization of feline abdominal lymph nodes. This study provides subjective and objective data on the CT characteristics of abdominal lymph nodes in 16 healthy cats, with younger cats having larger abdominal lymph nodes and a higher number of sacral lymph nodes.